Vaginal microbiota changes of persistent human papillomavirus infection after cervical conization - Liang, Lingyun; Ma, Cailing; Li, Yan; Mijiti, Yilidana; Zhang, Lipeng; Liu, Yanjia (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveWe investigated the changes in vaginal microbiota among females with persistent human papillomavirus (HPV) infection following cervical conization in Xinjiang, China.MethodsA total of 108 female participants were enrolled in the study, including 37 HPV-positive females without cervical conization (Group P1), 37 HPV-positive females after cervical conization (Group P2), and 34 HPV-negative females after cervical conization (Group N). DNA was extracted from vaginal secretions, and the V3-V4 regions of bacterial 16S rDNA were amplified and sequenced using NovaSeq technology. The diversity analysis of the bacterial microbiota was conducted using QIIME2 and R software, while the phenotypic analysis was performed with Bugbase software.ResultsLactobacillus was the predominant genus in the vaginal microbiota of women with persistent HPV infection after cervical conization in Xinjiang. Following partial cervical resection, the α-diversity of the vaginal microbiota decreased, particularly among patients who had cleared HPV. Bacterial vaginosis-associated anaerobes were common in the vaginal environment, with their relative abundance increasing in cases of persistent HPV infection. Postoperative persistent HPV infection was found to be correlated not only with pathogens linked to bacterial vaginosis but also with those associated with aerobic vaginitis. Gardnerella and Atopobium, as well as Bifidobacterium and Streptococcus, demonstrated a symbiotic synergy. Both Lactobacillus and Gardnerella exhibited negative correlations with many pathogenic bacteria. Anaerobic and biofilm formation were the most evident phenotypes in individuals with persistent HPV infection after conization.ConclusionThe vaginal microbiota of women with persistent HPV infection following cervical conization is characterized by the coexistence of Lactobacillus dominance and increased microbial diversity. Anaerobic bacteria and biofilm formation may play a significant role in the persistence of HPV infection post-surgery, and the role of Gardnerella in the vaginal flora under an HPV-infected state warrants further study.